Diversity of river fishes influenced by habitat heterogeneity across hydrogeomorphic divisions. (3rd July 2018) - Spurgeon, J. J.; Pegg, M. A.; Parasiewicz, P.; Rogers, J.
Abstract: Freshwater fish communities are structured through complex interactions among multiple spatial scales. Efforts to conserve and rehabilitate fish communities in riverine systems can benefit from an understanding of how processes across spatial scales influence species diversity patterns. We assessed species diversity at different hierarchical spatial scales and changes in species composition along the longitudinal gradient of the Niobrara River basin, Great Plains, USA. We assessed the contribution of α‐ and β‐diversity components to γ‐diversity at five spatial scales (i.e., mesohabitat, site, reach, segment, and river) using an additive partitioning approach. The observed mean β‐diversity was significantly greater than expected at the site, reach, and segment spatial scales. The most significant difference between expected and observed β‐diversity occurred at the segment spatial scale and suggests differences in community structure along the Niobrara River. Additive partitioning of diversity components provided a framework with which to assess patterns at multiple hierarchical levels. Our results suggest that changes in channel geomorphic and hydrologic conditions provide the impetus for species sorting resulting in unique fish assemblages along the Niobrara River. Conservation of species diversity for Great Plains fishes and other similar systems will likely benefit from considering species filtering processes at multiple spatial scales and maintaining intact hydrologic regimes across unique geomorphic boundaries.